Bacterial culture and antimicrobial susceptibility results from bovine milk samples submitted to four veterinary diagnostic laboratories in Australia from 2015 to 2019 - Langhorne, Charlotte; Gupta, Suman Das; Horsman, Sara; Wood, Caitlin; Wood, Benjamin J.; Barker, Leslie; Deutscher, Ania; Price, Rochelle; McGowan, Michael R.; Humphris, Mark; Ranjbar, Shahab; Henning, Joerg; et al. (Frontiers in Veterinary Science, 2023)
A 5-year retrospective study was conducted to describe the mastitis-causing organisms isolated from bovine milk samples submitted to four veterinary diagnostic laboratories in Australia. The aim was to identify temporal, geographical, and seasonal patterns of occurrence for the organisms and report the in vitro susceptibility of the most common mastitis-causing pathogens. In total, 22,102 milk samples were submitted between 2015 to 2019. Results were reported as positive growth for at least one significant organism (n = 11,407; 51.6%), no growth (n = 5,782; 26.2%) and mixed/contaminated growth (n = 4,913; 22.2%). Culture results for no growth, gram-negative bacteria and eukaryotic organisms were combined for each region and accounted for between 23% and 46% of submissions. These results represent a subset of mastitis cases for which antibiotic treatment may not be warranted. A total of 11,907 isolates were cultured from 11,407 milk samples. The most common organisms isolated were Streptococcus uberis (41.3%; 95% Confidence interval (CI): 40.4 -42.1%) and Staphylococcus aureus (23.6%; 95% CI:22.8 -24.3%). For S. uberis and S. aureus there was an association between a positive culture result and dairy region. All regions except the Sub-tropical Dairy region were more likely to culture S. uberis compared to the reference, Dairy NSW (P < 0.001).Similarly, for S. aureus, a positive culture result was more likely in all other dairy regions compared to Dairy NSW (P < 0.001). LISA cluster analysis identified differences between High-High (hotspot) postcodes for S. aureus and S. uberis throughout all the analyzed dairy regions. These results highlight a need for further investigations into specific risk factors such as environmental factors and herd-level predictors, which may have influenced the observed regional variations. Common mastitis-causing pathogens showed overall good susceptibility to a range of antimicrobials used in the treatment of mastitis. On-going surveillance of mastitis-causing pathogens and their antimicrobial susceptibilities will facilitate targeted mastitis control and treatment programs.